Significant Records of Birds in Smaller Islands in Palawan, Philippines - Paguntalan, Lisa J.; Jakosalem, Philip Godfrey; Bonares, Bernard; Oquendo, Maria Feliza Janet (Silliman Journal, 2022)
We documented, for the first time, the birds of Cambari Island and Green Island Bay in Palawan from May 2016 to January 2020. Using a combination of direct observations, area search and photo-documentation, we recorded a total of 64 birds including three threatened species, three near-threatened birds and 22 migrants. Species composition varied between islands and bird diversity ranged from 1.14 – 2. 85 (ShannonWeiner Index). Puerco Island (popularly known as Banwa Private Island) serves as an important breeding habitat of the Near-endemic Philippine Scrubfowl Megapodius cumingii and Mantanani Scops Owl Otus mantananensis. Small islands with beach forest and mudflats serve as temporary refuge for migratory species including rare and threatened species. Protection of breeding habitats and integration of native beach forests trees increased bird species richness.